2003
DOI: 10.1200/jco.2003.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Use of Genetic Testing and Prophylactic Mastectomy and Oophorectomy in Women With Breast or Ovarian Cancer From Families With a BRCA1 or BRCA2 Mutation

Abstract: In a clinical setting, we show a high demand for BRCA1/BRCA2 testing and for prophylactic surgery by women with breast and/or ovarian cancer from high-risk families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
3
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 33 publications
5
64
3
7
Order By: Relevance
“…This high percentage is related to various factors: 1) most women were index cases; 2) due to the high risk of BC, many relatives carrying a BRCA1 mutation and, to a lesser extent, relatives carrying a BRCA2 mutation, had already developed BC at the time of SO; or 3) women with a history of BC more readily accept SO. As shown in the studies by Scheuer et al 38 and Meijers-Heijboer et al, 39 prophylactic SO has been demonstrated to offer about a 50% reduction of the risk of either a first BC in women with no previous BC or contralateral BC in women with a previous BC. 10,11,[20][21][22] In the present series, 7 BCs occurred after SO: 3 BCs among the 16 women with no personal history of BC, and 4 contralateral BCs among patients with a history of BC.…”
Section: Discussionmentioning
confidence: 90%
“…This high percentage is related to various factors: 1) most women were index cases; 2) due to the high risk of BC, many relatives carrying a BRCA1 mutation and, to a lesser extent, relatives carrying a BRCA2 mutation, had already developed BC at the time of SO; or 3) women with a history of BC more readily accept SO. As shown in the studies by Scheuer et al 38 and Meijers-Heijboer et al, 39 prophylactic SO has been demonstrated to offer about a 50% reduction of the risk of either a first BC in women with no previous BC or contralateral BC in women with a previous BC. 10,11,[20][21][22] In the present series, 7 BCs occurred after SO: 3 BCs among the 16 women with no personal history of BC, and 4 contralateral BCs among patients with a history of BC.…”
Section: Discussionmentioning
confidence: 90%
“…Other studies of interest in genetic testing obtained interest ranging from 20% to 95% among women at risk of breast cancer while actual test uptake and returning for disclosure were considerably less. 17,23,30,[87][88][89][90][91][92] A recent systematic review of uptake rates for breast cancer genetic testing found a mean hypothetical uptake of 66% and mean actual uptake of 59%. 93 Stated interest has also been high with lower actual uptake for colon cancer, Huntington's disease, Alzheimer's disease and alcoholism.…”
Section: Discussionmentioning
confidence: 99%
“…Although BRCA1 and BRCA2 mutation carriers' cancer risks are increased [2,3], evidence suggests that these risks can be managed effectively [4][5][6][7]. While ovarian screening in high-risk groups is not effective, breast cancer screening is indicated and there is evidence of increased sensitivity of magnetic resonance imaging (MRI) for detecting malignancies in younger BRCA carriers [8,9], compared to mammography.…”
Section: Introductionmentioning
confidence: 99%